Javanese Language Skill Level of Early Childhood in Term of the Use of Javanese Song - Maulida, Fajar Rizky; Eka, R Agustinus Arum (Universitas Negeri Semarang, 2014)
This Study using experimental approach with Static Group Comparison. This study examined the difference of Javanese language skill for early childhood in Pekalongan city by singing method using Javanese songs. The sample of this study is 30 children of ABA Binagriya Kindergarten as experimental group and 30 children of ABA Bendan Kindergarten as control group. The Javanese songs was used with experimental group only. The result of the study were analized using t-test. Independent sample t test used to measure difference level of Javanese language skill. The result of Independent sample t test indicated that t count value is -6,350 and t table is 3,156. The value of –t count < -t table (-6,350 < -3,156. The study indicated that there are significant differences in mean scores of Javanese language skill.How to citeMaulida, F., & Eka, R. (2014). Javanese Language Skill Level of Early Childhood in Term of the Use of Javanese Song. Indonesian Journal Of Early Childhood Education Studies, 3(1), 42-46. doi:10.15294/ijeces.v3i1.9475